Development of a human scFv antibody targeting the lethal Iranian cobra (Naja oxiana) snake venom. (5th December 2019) - Kazemi-Lomedasht, Fatemeh; Yamabhai, Montarop; Sabatier, Jean-Marc; Behdani, Mahdi; Zareinejad, Mohammad Reza; Shahbazzadeh, Delavar
Abstract: Snakebite is one of the health concerns worldwide. Naja oxiana is one of the venomous snakes with a high mortality rate. Anti-serum therapy is the only treatment of the victims. However, in some cases, antiserum injection leads to some side effects in host like serum sickness and anaphylactic shock. It is crucial to develop a neutralizing agent with low side effects. The human antibody library (non-immunized library) was used to isolate specific antibodies against N.oxiana venom components. Four rounds of biopanning were performed to enrich scFv-displaying phages against the venom of N. oxiana . Enrichment of scFv-displaying phages against N. oxiana venom was analyzed by polyclonal Enzyme-Linked Immunosorbent Assay (ELISA). Specific antibody fragments against N. oxiana venom were selected through monoclonal ELISA, and were expressed in E. coli bacterial cells. Purification of the selected clones was performed by using nickel affinity chromatography. Neutralization and protective capacity of specific antibody fragments were analyzed in C57BL/6 mice (i.v. injection). Results of biopanning and polyclonal ELISA demonstrate a successful enrichment process. Five specific antibody fragments with the highest signal in monoclonal ELISA were selected, expressed, and purified. The purity of expressed antibody fragments was monitored by SDS-PAGE and Western blot. The selected antibody fragments were able to neutralize two LD50 of N. oxiana venom and protected all mice when injected 15 min post-envenomation. The data indicate that such selected antibodies are promising tools for further studies and in the development of novel protective agents against N. oxiana venom. Highlights: Non-immunized human antibody library was used to isolate specific antibody fragments (scFvs) against N. oxiana venom. Specific antibody fragments against  N.oxiana venom were selected through monoclonal ELISA. Neutralization and protective capacity of selected antibodies were analyzed in C57BL/6 mice. The selected antibodies protected all mice after 15 min envenomation.